2008
DOI: 10.1097/acm.0b013e318178356b
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Basic Sciences: An Innovative Approach to Teaching Senior Medical Students How Best to Integrate Basic Science and Clinical Medicine

Abstract: Abraham Flexner persuaded the medical establishment of his time that teaching the sciences, from basic to clinical, should be a critical component of the medical student curriculum, thus giving rise to the "preclinical curriculum." However, students' retention of basic science material after the preclinical years is generally poor. The authors believe that revisiting the basic sciences in the fourth year can enhance understanding of clinical medicine and further students' understanding of how the two fields in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 22 publications
2
104
0
4
Order By: Relevance
“…To diminish these problems, some have suggested altering the curriculum to ensure vertical integration, by initially teaching only clinically-oriented basic science subjects and then providing additional learning experiences in these subjects during the clinical years 79. The results showed a paradoxical association between students’ perception of receiving overloaded courses, being able to recall information, and receiving information that was applicable to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…To diminish these problems, some have suggested altering the curriculum to ensure vertical integration, by initially teaching only clinically-oriented basic science subjects and then providing additional learning experiences in these subjects during the clinical years 79. The results showed a paradoxical association between students’ perception of receiving overloaded courses, being able to recall information, and receiving information that was applicable to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, one question we have to face is to hunt for the optimal point-in-time for the integrated course. Some schools implement the integrated curriculum at the first-year students (Pipas, Peltier, Fall, Olson, Mahoney, Skochelak, & Gjerde, 2004), while some at the third-year or fourth-year students (Spencer, Brosenitsch, Levine, & Kanter, 2008). So far, there has not been evidence showing what time is the best to begin the integrated curriculum for medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Croen reported that the program of integration of basic science and clinical medicine for year 3 students at Albert Einstein College was successful since the students are able to apply basic science concepts and principles to clinical problems well (Croen, Lief, & Frishman, 1986). The reform program at University of Pittsburgh School of Medicine was to integrate basic science knowledge into clinical teaching during the fourth year of medical school, and the authors also thought that senior medical students are better able to appreciate the relevance of basic science concepts to clinical medicines (Spencer, Brosenitsch, Levine, & Kanter, 2008). The two reports are generally consistent with our observation in this study although they did not optimal time for open the integrated curriculum to the senior students with the junior students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations